Kajian Etnozoologi Biawak (Varanus salvator) dalam Bidang Kesehatan oleh Masyarakat Suku Anak Dalam (SAD) - Herawati Dwi Astuti; Laelatul Mukharomah; Lailatus Shobaiyah; Novita Novita (BioEksakta : Jurnal Ilmiah Biologi Unsoed, 2020)
Lizard or known as the Asian water lizard (Varanus salvator) is one of the reptiles found in Asia, one of which is in Indonesia. In addition to being used as food, some communities use monitor lizards to treat diseases, especially those who still maintain ancestral customs and beliefs. This study aims to describe the knowledge of local indigenous peoples in utilizing monitor lizards for the treatment of diseases and integrating them with traditional conservation efforts undertaken by the community. The research uses the ethnozoology approach through the literature review method. The results showed that the local people especially Suku Anak Dalam (SAD) in Jambi used monitor lizards for the treatment of skin diseases, hypo-allergies and ringworm by burning or cooking them using cooking oil until the fat in the monitor lizards melted for ointment. However, the local people still try to maintain the balance of monitor lizards by choosing large monitor lizards that are suitable for consumption, using simple hunting tools, and domestication efforts so that the monitor lizard population is maintained in a sustainable manner. This is known because the mechanism of hypo-allergenic treatment of monitor lizard meat has the potential to reduce the effects of allergies given by allergy in the form of histamine 1.5% by 10 ml. In conclusion, the use of monitor lizards in the field of health by the local community wisely can improve conservation skills through traditional ecological knowledge (Traditional Ecological Knowledge)